(untitled) (Journal of Philosophy, Culture and Political Science, 2022)
The last 10-15 years, the research of the practice of memory and places of memory has become relevant among scientists of social sciences and humanities. The French anthropologist Pierre Nora first put the concept of “memory places” forward. This article attempted to analyze the concepts of “places of memory and memorable places” in the series of articles by P. Nora “Between Memory and History: Les Lieux de Mémoire” (Nora, 1999). Researching the problems of historical memory and space, the authors examine the genealogy of memory research development and its impact on the origin of the concept of “place of”. Places of memory, according to P. Nora – “this is a place of spiritual and material unity that over time and by the will of people has become a symbolic element of the heritage of national memory or collective memory of people” (Nora, 1999: 26). Space plays a huge role in the creation of places of memory, that is, the territory where the monument is constructed, a memorial complex is built and a mazar is erected. The “cultural turn” that took place in the early 1970s in the social sciences allows to name it a cultural landscape. Relationship problem between culture and space, the semantic characteristics of space organization – a complex system of interrelated components. In the humanitarian knowledge, relationship problem between culture and space has been studied mainly in linguistic or anthropological discourses that do not consider the phenomenon of the cultural landscape in its entirety. In given article, the authors analyzing the concepts of memory places, determine the role of the cultural landscape as the keeper of historical and cultural memory, as the emotional capital of a certain territory. The article completed within the framework of a dissertation research on the topic “Cultural landscape: research problems”. Key words: memory places, cultural landscape, commemoration, historical memory, identity, forgetfulness.